EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP IT INSAN QURANI PONCOWARNO - Abu Munawar Sidik (UNISAN JURNAL, 2023)
This study aims to analyze and evaluate the management of the learning process of Islamic Religious Education at SMP IT Insan Qurani Poncowarno City. The research was conducted using a qualitative approach and data collection techniques through interviews, observation, and document studies. The results showed that the management of the learning process of Islamic Religious Education at SMP IT Insan Qurani Poncowarno City had been carried out well, where there were several aspects that had been managed properly such as lesson planning, learning implementation, assessment and evaluation, and curriculum development . However, there are several aspects that need to be improved such as the use of more varied and creative learning media, as well as the use of technology in the learning process. In this case, efforts are needed to develop and improve the management of the learning process of Islamic Religious Education at SMP IT Insan Qurani Poncowarno City, taking into account the needs and desires of students, as well as utilizing technology and learning media that are more innovative and effective. The results of this study are expected to provide input for the development and improvement of the management of the learning process of Islamic Religious Education at SMP IT Insan Qurani Poncowarno City, and can become a reference for other educational institutions